2009
DOI: 10.1143/apex.2.011202
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable Schottky Barrier Diode by Ru/Diamond

Abstract: For the high temperature operation of diamond for high power devices, a new Ru/diamond material contact was proposed for the first time for thermally stable Schottky barrier diode (SBD). This contact showed very good Schottky properties, with the further advantages of low resistivity, high chemical stability and very high adhesion characteristics. The devices were tested for thermal stability at 400 °C for 1500 h and 500 °C for 250 h. The SBD characteristics were highly stable, and after an initial stabilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 10 publications
3
45
0
Order By: Relevance
“…The calculated Schottky barrier height from eq. (2) with the use of effective Richardson constant A * = 90 Acm −2 K −2 in reference [10] is φ B = 1.2 eV at room temperature, which coincide with the value reported in reference [5]. Fig.…”
Section: Fig 2 Reverse Blocking Characteristicssupporting
confidence: 87%
See 1 more Smart Citation
“…The calculated Schottky barrier height from eq. (2) with the use of effective Richardson constant A * = 90 Acm −2 K −2 in reference [10] is φ B = 1.2 eV at room temperature, which coincide with the value reported in reference [5]. Fig.…”
Section: Fig 2 Reverse Blocking Characteristicssupporting
confidence: 87%
“…There are several reports on the development of electronic devices using diamond semiconductors, but there are few reports involving power switching devices. Reference [4,5] reported the static rectification characteristics of the p-type diamond Schottky barrier diode (SBD) and its temperature dependency; however, it did not evaluate the dynamic switching characteristics. The authors reported the dynamic switching characteristics of high voltage diamond SBD at room temperature in reference [6], but the conduction current was small (∼100 mA) because of the small active area of the device.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional models all assume a uniform dopant distribution, and it remains unclear how the composition and atomic structure of the semiconductor affect the electronic structure, i.e., barrier height and band bending, on the atomic level. It should be noted, however, that recent advances [96][97][98][99] have made it possible to characterize the Schottky band bending at the nanometer scale and have revealed important deviations from predictions made on the conventional Schottky model [100]. Instead, the results, which depend on materials' properties, dopant compositions and concentrations, can be qualitatively interpreted in the inhomogeneous Schottky barrier height model [101][102][103].…”
Section: Charge Carrier Transportmentioning
confidence: 99%
“…In the accelerated deterioration test, there were no changes over 1500 hours at 400 °C as shown in Figure 10, regardless of the presence or absence of defects. [20] It was estimated that ultra high thermal resistance of over 300 thousand hours at 250 °C should be obtained when the activated energy of deterioration by surface graphitization was assumed to be l eV. The search for such heat resistant Schottky metal was far from the originally planned R&D. However, by conducting the high-temperature deterioration test at an early stage, we were able to overcome the issue early so it would not be a major problem after the development had progressed for some time.…”
Section: ) Refractory Metalmentioning
confidence: 99%